Agricultural water balances in agroclimatic simulation models. An analytical review - Cleves L., José Alejandro; Toro C., Javier; Martínez B., Liven Fernando (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2016)
This article analyzes the applicability of the agroclimatic crop simulation models CropWat v 8.0 and AquaCrop in the occurrence of ENSO (El Niño-Southern oscillation) events and climate change. The importance of these models is significant because they help farmers implement management measures and locate cultivars taking into account climatic conditions, thus allowing their participation, from the territorial context, in the design and implementation of strategies for mitigation and/or adaptation. Different methodologies used for determining the reference evapotranspiration (ETo) were compared, and the attributes, characteristics and applicability with the Penman-Monteith equation were described. Finally, the variables of the agricultural water balance were determined, along with their applicability regarding the preservation or the increase of productivity in different scenarios. It was concluded that these models are essential technical tools for planning sowing and harvests.